Pemberdayaan Siswa-Siswi SMAS Bhaktyarsa sebagai Duta KONSER melalui Kelas Basic Konseling Pastoral: Pengabdian - Debi Angelina Br. Barus; Epifania M. Ladapase; Yuldensia Avelina; Agustinus Denny Widhayaka Raja; Fransesco Alexandro (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve students’ understanding and skills in maintaining mental health, as well as to equip them with basic pastoral counseling techniques through the Basic Pastoral Counseling class program. The program was attended by 20 students who were then formed into KONSER Ambassadors (Friendly Counselors) to support the school’s guidance and counseling services. The implementation method consisted of a basic pastoral counseling class comprising ten meetings, which included five material sessions and five counseling practice sessions, presentations, and the selection of KONSER Ambassadors. The materials provided covered eight modules: Child Development Psychology, Personality, EQ & SQ, People with Severe Mental Disorders (ODGJ), Trauma, Loving Until It Hurts, Self-awareness, and Self-healing & Self-counseling. After the completion of all activities, mentoring and evaluation were conducted. The results of the program showed an increase in students’ knowledge of mental health, basic counseling skills, and confidence in providing emotional support to their peers. In addition, two KONSER Ambassadors were appointed as part of the school organization, and innovative educational media in the form of podcasts and posters were produced and published through social media.